2023
DOI: 10.1149/1945-7111/ad0513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxalic Acid Additives on Aluminum Anodizing in Formic Acid Containing Ammonium Heptamolybdate

Katsiaryna Chernyakova,
Vaclovas Klimas,
Renata Karpicz
et al.

Abstract: We report on a systematic study of the role of oxalic acid additives in aluminum anodizing in formic acid containing ammonium heptamolybdate. Adding oxalic acid in a concentration range of 5–20 mM to the 0.4 M formic acid solution containing 0.03 M ammonium heptamolybdate improves anodic film growth, increasing the film thickness and smoothing strongly wavy interface between the film and aluminum, and adding 100 mM of oxalic acid results in an almost complete block of the regular anodic film formation. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, it was also shown that other additives to the electrolyte, like Cu(EDTA) 2 4− coordination anions [ 69 ], or even organic molecules, like indigo carmine [ 70 ], can be successfully incorporated and change properties of the oxides, i.e., optical. Chernyakova et al [ 71 , 72 ] have shown that anodizing high-purity Al in formic acid and formic acid with oxalic acid and molybdates facilitates the incorporation of carbon in the grown anodic alumina. The authors did not focus on the molybdate incorporation itself, but showed a strong impact of the molybdates on carbon incorporation.…”
Section: Incorporation Of Anions Into Anodic Aluminamentioning
confidence: 99%
“…Furthermore, it was also shown that other additives to the electrolyte, like Cu(EDTA) 2 4− coordination anions [ 69 ], or even organic molecules, like indigo carmine [ 70 ], can be successfully incorporated and change properties of the oxides, i.e., optical. Chernyakova et al [ 71 , 72 ] have shown that anodizing high-purity Al in formic acid and formic acid with oxalic acid and molybdates facilitates the incorporation of carbon in the grown anodic alumina. The authors did not focus on the molybdate incorporation itself, but showed a strong impact of the molybdates on carbon incorporation.…”
Section: Incorporation Of Anions Into Anodic Aluminamentioning
confidence: 99%